Ampeliscid crustaceans Ampeliscidae (Amphipoda - Gammaridea) from nearshore waters of Vietnam - Anh, Le Hung; Thanh, Dang Ngoc (Academia Journal of Biology, 2012)
﻿Ampeliscid crustaceans and amphipods at all of the Vietnam Sea, up to present times have been poorly studied. Only two publications appeared in the past time, by results of some surveys carried out in Nha Trang Bay (Imbach, 1967) and in Bac Bo Gulf (Tonkin Gulf) (Margulis, 1968). Totally in these above publications, 22 species of Ampelisca and 12 species of Byblis has been recorded, of these, many new species to science were described. The results of our taxonomical study on a great number of materials of benthic Ampeliscidae, collected from different representative localities of the nearshore waters of Vietnam in different times, has enlarged and ﻿adjusted the previous data, which give a comprehensive knowledge on the Ampeliscidae species composition of the Vietnam Sea. By geographical distribution aspect, fauna Amphipoda Ampeliscidae of Vietnam sea may be divided into 3 groups: 1. Group species cosmopolitan or enlarge distributed in Indo-Pacific region (Ampelisca cyclops, A. brevicornis, A. miops, A. zimboangae Byblis rhinoceros, B. mucronata...); 2. Species with restricted distribution in West Pacific region (Ampelisca bocki, A. misakiensis, A. misaharensis, A. iyoensis, Byblis io, B. pilosa, B. plumosa, B. pirloti, B. callisto...); 3. Species up to now found only in Vietnam Sea (Ampelisca dongnamensis, A. thaoae, Byblis caecus...). In this area, 11 species are newly recorded for the benthic Ampeliscidae fauna of the Vietnam Sea, of which 6 species are new to science (5 Ampelisca, 1 Byblis). Some remarks on the geographical distribution and taxonomical characteristics of the ampeliscid fauna of the Vietnam Sea are presented in the paper.